Sleeping with the enemy NET and Java living together. - Down, Fred (SOA webservices journal.)
People often assume the .NET and J2EE are locked in some kind of life and death struggle. In fact, they can co-exist very well as I proved on a recent project. Both .NET and J2EE are based on open standards; these are Web Services Definition Language (WSDL) and Simple Object Access Protocol (SOAP), both of which are built on Extensible Markup Language (XML). This article describes how a .NET Web Services application was cloned using Java to run on a variety of Unix platforms.